EVALUASI PROGRAM PENINGKATAN KAPASITAS USAHA POKLAHSAR DALAM MENINGKATKAN PENDAPATAN MASYARAKAT PESISIR DI KABUPATEN PANGKEP - Irawati, Risna; Rauf, Muhammad; Djafar, Syahrul (Universitas Negeri Makassar, 2018)
This study aims to determine the factors that affect the income generation of processing group of fishery products in coastal Pangkep regency. Knowing the income level of the group of fishery producers who have received assistance or who have not received assistance from the Director General of Strengthening Maritime and Fishery Competitiveness in Pangkep Regency. This research was conducted in February until March 2018 in coastal area of Pangkep Regency. Data collection using t test analysis is comparative test. The results of multiple regression analysis show that the role of government variable has t arithmetic 2.278> t table of 2.2015 (sig. Α = 0,05 and df = nk, that is 15-4 = 11), unstandardized beta coefficient of 0.258 and significance level of 0.044 <0.05. This shows that the role of government affects the income of fishery product processing business group. economic variable has t count 2,450> t table equal to 2,2015 (sig. α = 0,05 and df = nk, that is 15-4 = 11) with unstandardized beta coefficient of 0,139 and level of significance 0,032 smaller than 0,05 . This shows that the economy affects the income of fishery product processing business group. While the socio-cultural variables have t arithmetic equal to -1.259 <t table of 2.2015 (sig. Α = 0,05 and df = nk, ie 15-4 = 11) with unstandardized beta coefficient of -0.167 and the significance level -0.154 greater than 0.05. This shows that social culture does not affect the income of fishery product processing business group.